BUSINESS DEVELOPMENT PLAN FOR COFFEE TRAINING AT CH3FFEIN COFFEE RESEARCH AND DEVELOPMENT UNIT - Katharina Veronika; Meriza Hendri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The growth of Indonesia's coffee industry has led to an increase in coffee MSMEs, baristas, and coffee shops, yet there remains a gap in structured, practice-based coffee training. In response, the Ch3ffein Coffee Training Unit aims to develop a business plan for a research-based training center. Methods: This study focuses on formulating a business plan for the Ch3ffein Coffee Training Unit by: first, analyzing Ch3ffein's business strategy using the Design Thinking approach, Business Model Canvas, Lean Canvas, and Entrepreneurial Process to create effective development strategies; second, developing a business plan from the perspectives of finance, marketing, operations, human resources, digitalization, innovation, and risk management, based on a SWOT analysis; and third, evaluating the business feasibility using the Timmons Model and financial indicators like Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Profitability Index. The study adopts a qualitative descriptive method, using observation, unstructured interviews, document reviews, and secondary data analysis related to the coffee industry and MSME development. Results: Financial projections show positive results, with a favorable NPV, rate of return, short payback period, and Profitability Index above one, indicating solid financial feasibility. Ch3ffein benefits from competitive advantages in its research and laboratory base, operational flexibility, and strong connections within the coffee industry and MSMEs. The development of this training unit offers significant opportunities for both business growth and social impact by supporting the improvement of competencies and competitiveness among coffee MSMEs. Recommendations include strengthening instructor capacity, gradually upgrading facilities, and expanding strategic collaborations with industry stakeholders to ensure long-term sustainability. Keywords: Business Planning, Coffee MSMEs. Coffee Training Unit